Critique to Capitalism in The Little Prince Film: A Marxist Approach - Muhammad Yusfan Gofiqi (Passage, 2018)
This paper aims to analyze The Little Prince film using Marxism. The Little Prince film was released in 2015 with Mark Osborne as the director. This film was adapted from its book, but it tells the story from a different angle, which in turn changes the meaning of the film in some ways. A number of issues in the film can be analyzed from Marxism. The Little Prince film appears to highlight current thinking adopted by the society about work. Specifically, employing a qualitative research approach, this paper reveals the various representations of capitalism embedded in the film and the social class distinction that is portrayed. The analysis is expected to raise critical awareness among the audience of the ideologies embedded in the film. Keywords: The Little Prince, film, Marxist approach, capitalism, social class